2021
DOI: 10.1089/heq.2021.0035
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Health Equity in Emergency Care Using Routinely Collected Data: A Systematic Review

Abstract: Introduction: Achieving equity in health care remains a challenge for health care systems worldwide and marked inequities in access and quality of care persist. Identifying health care equity indicators is an important first step in integrating the concept of equity into assessments of health care system performance, particularly in emergency care. Methods: We conducted a systematic review of administrative data-derived health care equity indicators and their association with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 49 publications
(83 reference statements)
0
26
0
2
Order By: Relevance
“…Another important factor to consider when using quality metrics to guide quality improvement is how using different measures for the same concept can reflect different aspects of healthcare quality. For example, a recent review identified 14 unique ESU measures from 29 studies [ 39 ]. The authors concluded that the number or frequency of use of emergency services was believed to measure accessibility, whereas the time between arrival to the emergency department and diagnosis or treatment was believed to measure timeliness [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another important factor to consider when using quality metrics to guide quality improvement is how using different measures for the same concept can reflect different aspects of healthcare quality. For example, a recent review identified 14 unique ESU measures from 29 studies [ 39 ]. The authors concluded that the number or frequency of use of emergency services was believed to measure accessibility, whereas the time between arrival to the emergency department and diagnosis or treatment was believed to measure timeliness [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent review identified 14 unique ESU measures from 29 studies [ 39 ]. The authors concluded that the number or frequency of use of emergency services was believed to measure accessibility, whereas the time between arrival to the emergency department and diagnosis or treatment was believed to measure timeliness [ 39 ]. A review of cancer survivors' healthcare utilization patterns identified that it was not just the number of healthcare visits that were associated with the quality of healthcare but also the type of provider and the number of patients shared between providers [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the problems with hospital safety monitoring systems already noted in the literature, recent research is showing that they may not capture critical details about equity (eg, race/ethnicity, religion, sex, gender, income, financial barriers, disability21 26–28) that would make explicit the ways that equity-related factors influence safety practices and events. For instance, studies have reported race differences in adverse event occurrence by type and hospital setting6 and that voluntary incident reporting systems may underdetect safety issues in marginalised populations 5.…”
Section: Introductionmentioning
confidence: 99%
“…Overtime, for moderately deprived patients, several interventions may also be needed. Studying the appropriateness of health care pathways is a new challenge to fit health services with the patient resources and needs [58,59].…”
mentioning
confidence: 99%